2017
DOI: 10.18410/jebmh/2017/1187
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Fractional Co2 Laser and Dermaroller in the Treatment of Atrophic Facial Acne Scars

Abstract: BACKGROUNDAtrophic scars results from any inflammatory skin disease causing sufficient damage to epidermis and dermal collagen. The most common causes of atrophic scars are severe nodular or nodulocystic acne. Main morphological types of atrophic post-acne scars are icepick scars, superficial or deep boxcar scars and rolling scars and various modalities of treatments are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…All the patients in fractional CO 2 laser group showed improvement, of which 80% improved by 1 grade and rest 20% by another 2 grades in Goodman and Baron qualitative scar grading scale. 14 In this study, on comparing of the efficacy of the derma roller and the fractional CO 2 laser resurfacing treatment significant results have been shown individually. It has been shown that all types of scars at all stages have been reduced and removed by both the methods.…”
Section: Discussionmentioning
confidence: 90%
“…All the patients in fractional CO 2 laser group showed improvement, of which 80% improved by 1 grade and rest 20% by another 2 grades in Goodman and Baron qualitative scar grading scale. 14 In this study, on comparing of the efficacy of the derma roller and the fractional CO 2 laser resurfacing treatment significant results have been shown individually. It has been shown that all types of scars at all stages have been reduced and removed by both the methods.…”
Section: Discussionmentioning
confidence: 90%
“…The percentage reduction achieved by fractional CO 2 laser was higher for severe scars, compared to dermaroller therapy and the difference was found to be statistically significant. These results were confirmed by study of Chawla, 2014 indicating that fractional CO 2 laser treatment is a new treatment for post acne scars it is better [14] . The good degree of improvement after CO 2 laser resurfacing was attributed to its mode of action which incorporate tissue removal, prompt collagen shrinkage, and remodeling of dermal collagen.…”
Section: Discussionmentioning
confidence: 54%
“…However derma roller has lesser down time and very few complications as compared to CO2 fractional laser which has higher downtime and grave complications of post inflammatory hyperpigmentation. 18 Badheka et al, in 2016 did a study to compare the efficacy of subcission, CO2 fractional laser and dermaroller (microneedling) in acne scars and concluded that outstanding response was seen in 13.33%, 20% and 6.7% patients in the above treatment groups respectively. He concluded that CO2 laser was better than subcission which in turn was better than dermaroller in terms of efficacy.…”
Section: Discussionmentioning
confidence: 99%